MRI in Management of Mild TBI/Concussion in the Deployed Setting. (5th September 2018) - Marion, Donald W; Grimes, Jamie B; Hinds II, Sidney R; Lewis, Jeffrey; Baugh, Laura; Stockinger, Zsolt T
Abstract: Magnetic resonance imaging (MRI) has specific limitations in theater and has unique requirements for its safe use with patients which require additional technician training and strict adherence to MRI-specific safety protocols. Neuroimaging is recommended for the evaluation of service members with clinical red flags new onset or persistent or worsening symptoms, and individuals whose recovery is not progressing as anticipated. This article is a brief discussion of when MRI is appropriate.